Nonlinear integrable systems related to the elliptic lie—baxter algebra - Pritula, N. N.; Sidorenko, Yu. M.; Strampp, W. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We construct a hierarchy of Poisson Hamiltonian structures related to an “elliptic” spectral problem and determine the generating operators for the equation of asymmetric chiral 0 (3) — field.